Sense of Gloominess and Despair in Edgar Allan Poe’s Selected Poems: : An Analytical Approach - Hasan, Mariwan; Karim, Rayan; Muhsin, Sara (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2024)
Edgar Allan Poe's life was plagued by melancholy and disaster, which is evident in all of his writings. Among the many other poets of his generation, his solitude and individuality set him apart from the rest. He gave the Gothic genre a completely new meaning, making it both dark and significant at the same time. First, as an overview is given, of the 19th century, Edgar Allan Poe, and the tragedies that influenced his poetry. This study employs a comprehensive methodology focusing on the close reading of three of Poe's well-known poems: "The Raven," "A Dream within a Dream," and "Alone." By analyzing how sadness and sorrow are portrayed in these poems, the paper investigates the extent to which these emotions impacted Poe's writing. The analytical approach involves delving into the thematic and stylistic nuances of the selected poems, shedding light on the intricate ways in which Poe articulates his emotions. The purpose of this study is to tackle the sense of gloominess and sadness by employing textual and analytical approaches. The significance of the feelings of loss and sorrow in Poe's writings is addressed, drawing connections to Poe's life story. The findings demonstrate that Poe's writings occasionally converge with personal catastrophes, tragedies from his own life, and stories about death sadness, and grief come together on multiple occasions over the course of his demanding career. Concluding that sadness, sorrow, and everything that comes with it were indeed lurking in every one of his statements, this paper contributes to the existing literature by portraying the semi-autobiographical image of the author within the realm of his poetry. The textual and analytical approaches used in this study provide a nuanced understanding of how personal experiences influenced Poe's poetic expression, enriching our comprehension of the intricate relationship between his life and art.